An integrated economy‐demography model reframed in a system dynamics setting. (27th February 2020) - Dural‐Selcuk, Gozdem; Tunc, Huseyin; Tarim, S. Armagan
Abstract: In recent history, there has been an increasing concern about population aging and the associated increased economic burden in terms of high health‐care expenses and pension payments. The need for decision support tools that can explore population dynamics has become a prominent issue. This study presents a comprehensive framework where one can scrutinize the key demographic drives of fertility (Total Fertility Rate/Age‐Specific Fertility Rate) over macroeconomic indicators (technology, education, human capital) under exogenous mortality. The integrated model in this article is developed based on a reformulation of the unified growth theory. In the reformulated model, namely the "economy‐demography model, " the population age/sex structure is preserved, age‐specific mortality is included, and fertility is measured in conventional demographic terms. The model is then presented in system dynamics framework, and its practical use is showcased with data obtained from the Turkish Statistical Institute. Copyright © 2020 System Dynamics Society